The risk of total mortality and cardiovascular mortality associated with impaired glucose regulation in Tayside, Scotland, UK: a record-linkage study in 214 094 people. Issue 1 (16th September 2015) - Evans, Josie M M; Eades, Claire E; Leese, Graham P
Abstract : Objective: Mortality among adults of all ages diagnosed with impaired glucose regulation (IGR) in Tayside, Scotland, UK, was evaluated using routinely collected healthcare data sets. Research design and methods: Using record-linked data in 2003–2008, all instances of blood glucose testing in the population defined 2 cohorts of patients aged 18+years: those with IGR (whether impaired fasting glucose or impaired glucose tolerance (IGT)) according to the WHO criteria, and those who were normoglycemic. They were followed in survival analyses for mortality or cardiovascular mortality (censoring deaths that occurred within a 30-day period of testing), to derive HRs (with 95% CI) for IGR status using Cox regression, adjusted for age, sex, and an area measure of deprivation. Results: There were 2 372 712 tests for 214 094 patients, with 196 799 patients in the non-IGR cohort and 50 080 in the IGR cohort. During follow-up, 19 147 (9.7%) and 8397 (16.8%) patients died in 2 cohorts, respectively, with mortality rates of 33.2/1000 patient-years and 70.7/1000 patient-years. In multivariable analyses, the overall adjusted risk of mortality for IGR was 1.16 (95% CI 1.13 to 1.20). However, it was 2.59 (95% CI 2.17 to 3.10) for people aged <45 years, decreasing to 0.94 (95% CI 0.85 to 1.00) in those aged 85+years. The HRs for cardiovascular mortality were lower overall, but they followed the same pattern, with statistically significant increased risks for patients aged <64 years only. The mortality risk was highest among patients with IGT. Conclusions: IGR is associated with an increased mortality risk which declines with age. It is therefore important to prioritize young people with IGR for prevention; but less important to be aggressive about risk factor modification in older people.